Generating trust in participatory research on plasmodium knowlesi malaria: A study with rural community gatekeepers during the covid-19 pandemic - Nurul Athirah Naserrudin; Richard Culleton; Pauline Yong Pau Lin; Sara Elizabeth Baumann; Rozita Hod; Mohammad Saffree Jeffree; Kamruddin Ahmed; Mohd Rohaizat Hassan (MDPI, 2022)
Plasmodium knowlesi malaria is a zoonotic infection that affects rural communities in South East Asia. Although the epidemiology of the disease has been extensively researched, the voices of individuals within affected communities often go unheard. Here, we describe a study that explores the importance of gatekeepers in conducting research among rural communities, their perspectives on the challenges encountered when attempting to avoid malaria infection, and their views on participatory research. Methods: Between 1 November 2021 and 28 February 2022, we conducted a study in Kudat district, Sabah, using a multi-method design. All participants consented to the study, which included health care workers (HCWs) (n = 5), community leaders (n = 8), and faith leaders (n = 1). We conducted interviews, transect walks, and observations with gatekeepers to ensure data trustworthiness. All interviews were conducted in the Sabah Malay dialect. The sessions were audio- and video-recorded, transcribed into English and analyzed using thematic analysis. Results: Between 2017 and 2021, the number of cases of P. knowlesi malaria detected in humans ranged from 35 to 87 in villages under the care of the Lotong primary health care clinic. The challenges in controlling malaria include social norms, lifestyles, socioeconomic factors, environmental factors, and limitations of basic resources. Critical discussions regarding participation with the gatekeepers identified that face-to-face interviews were preferable to online discussions, and influenced willingness to participate in future research. Conclusion: This study was conducted among village gatekeepers during the COVID-19 pandemic and generated information to drive methodological changes, opening up new ideas by sharing perspectives on challenges in P. knowlesi malaria control among vulnerable communities. The study generated trust in the community and expanded knowledge regarding participation that is critical for future community-based studies.